Development of a 3D bioprinting and standalone bioreactor unit for the production and maintenance of bioscaffolds in vitro - Hundling, Jethro Daniel (Rhodes University, Faculty of Science, Biotechnology Innovation Centre)
The most common method for in vitro cell culture currently is to grow a specific cell type in isolation, in monolayer format, adhered to a 2D culture surface. This brings about many limitations in comparison to in vivo models due to altered cell phenotypes, as caused by the culturing technique itself, and the lack of naturally occurring cell-to-cell interactions. Three dimensional mammalian cell culture technologies have the potential to overcome these limitations, and provide models more representative of natural systems. Unfortunately, the cost and difficulty associated with achieving sustainable and useful 3D mammalian cell culture is still very high, preventing its widespread adoption across scientific platforms. In this research, we investigate the feasibility of developing and producing a visible light-based 3D stereolithographic bioprinter to produce 3D scaffolds for cell culture. Furthermore, we investigate the possibility of developing and implementing a forced perfusion bioreactor system, which would support the produced scaffold and improve longer-term culture conditions. The developed 3D bioprinter, and bioreactor designs were developed and tested alongside Poly (ethylene glycol) diacrylate (PEGDA), a versatile synthetic scaffold material. PEGDA itself was also evaluated for its printability, robustness in culture conditions over time, and its ability to maintain 3D mammalian cell culture. This research showed that both the developed 3D bioprinter, and bioreactor unit were capable of producing and maintaining an easily modifiable PEGDA scaffold, in culture conditions. In addition, the PEGDA formulation developed was shown to allow for the effective and reproducible 3D cell culture conditions over the medium term, with automated media feeding. The research presented here aimed to illustrate a proof of concept that the low-cost development and production of 3D culture scaffold production and maintenance systems was feasible to the scientific research environment. This technology can then be built upon, into a system that would then allow for the broader adoption and investigation of 3D cell culture as a tool within the scientific community.
Keywords: Bioreactors; Tissue scaffolds; Cell culture; Polyethylene glycol Biotechnology; 3D bioprinting; Poly(ethylene glycol) diacrylate (PEGDA)